2016
DOI: 10.1093/eurheartj/ehw119
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability causes atrial fibrosis and promotes atrial fibrillation

Abstract: The hypercoagulable state during AF causes pro-fibrotic and pro-inflammatory responses in adult atrial fibroblasts. Hypercoagulability promotes the development of a substrate for AF in transgenic mice and in goats with persistent AF. In AF goats, nadroparin attenuates atrial fibrosis and the complexity of the AF substrate. Inhibition of coagulation may not only prevent strokes but also inhibit the development of a substrate for AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 39 publications
5
100
1
4
Order By: Relevance
“…Several recent studies [14,20,[23][24][25] have demonstrated that DOACs can directly modulate the mechanical and electrophysiological properties of the LA and PVs and suggest that DOACs may have a beneficial effect of anti-AF actions via preventing AF progression in addition to their anti-thrombotic action. Therefore, DOACs may affect the natural course of AF progression causing a transition from a paroxysmal to persistent form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies [14,20,[23][24][25] have demonstrated that DOACs can directly modulate the mechanical and electrophysiological properties of the LA and PVs and suggest that DOACs may have a beneficial effect of anti-AF actions via preventing AF progression in addition to their anti-thrombotic action. Therefore, DOACs may affect the natural course of AF progression causing a transition from a paroxysmal to persistent form.…”
Section: Resultsmentioning
confidence: 99%
“…Spronk et al investigated the effects of hypercoagulability and its suppression of AF remodeling using several animal models [23]. In isolated rat atria preparations, the authors found that thrombin enhances the expression of the pro-fibrotic factor, transforming growth factor β1, and pro-inflammatory substance monocyte chemoattractant protein-1, and also increases the incorporation of 3H-proline, suggesting an increased collagen synthesis by fibroblasts.…”
Section: Beneficial Effects Of Doacs On the Electrophysiological Propmentioning
confidence: 99%
“…A PF idején fennálló ischaemia aktiválja az alvadási faktorokat, amelyek proteáz aktiválta receptorokat (PARs) stimulálva szívizomsejt-hypertrophiát, gyulladásos reakciót, valamint fibroblastaktiváció talaján pitvari fibrosist idéznek elő. A fokozott alvadékonyság által aktivált folyamatok a pitvarok strukturális remodellációját előidéz-ve megzavarják a szívizomrostok közötti ingerületveze-tést, és ezáltal a PF szubsztrátjául szolgálnak [5,43].…”
Section: Fokozott Alvadékonyságunclassified
“…Mindezek az adatok arra utalnak, hogy a fokozott alvadékonysággal járó állapotok-nak szerepük lehet a PF-szubsztrát kialakulásában. A NOAC-ok eredményesen gátolják a pitvari fibroticus folyamatokat és a PF szubsztrátjának kialakulását, ezáltal késleltethetik a PF progresszióját, továbbá a pitvari thrombusképződést és a következményes stroke kialakulását [43].…”
Section: Fokozott Alvadékonyságunclassified
“…26 New anticoagulant therapy can inhibit PAR1 activation and through it can prevent the development of a substrate for AF. 27 A CHADS2 and CHA2DS2-VASC score of 0 may be insufficient to avoid thromboembolism events in patients with AF. 28 More information about thromboembolic risk can be obtain by determination of the level of troponin I, CRP, and NT-pro BNP.…”
Section: Introductionmentioning
confidence: 99%